Dysfunction of the limbal epithelial stem cell niche in aniridia-associated keratopathy: Limbal niche in aniridia-associated keratopathy - Schlötzer-Schrehardt, Ursula; Latta, Lorenz; Gießl, Andreas; Zenkel, Matthias; Fries, Fabian N.; Käsmann-Kellner, Barbara; Kruse, Friedrich; Seitz, Berthold (Ocular Surface, 2021)
Purpose: Abnormalities in the limbal niche microenvironment have been suggested to be causally involved in aniridia-associated keratopathy (AAK), but histological analyses on the limbal structure and composition in AAK are lacking. Here, we investigated morphologic and molecular alterations of the limbal epithelial stem cell niche in human congenital aniridia. Methods: The blind, buphthalmic and painful left eye of a 16-year old girl with congenital aniridia and juvenile glaucoma had to be enucleated because of uncontrolled intraocular pressure. The diagnosis of AAK was based on classical clinical features and partial limbal stem cell deficiency in the superior half. Genetic analysis identified a large heterozygous PAX6 gene deletion encompassing exons 11–15 as well as exon 9 of the neighboring ELP4 gene. Three limbal biopsies were taken from the superior, nasal and temporal regions to isolate and cultivate limbal epithelial progenitor cells and subject them to mRNA expression analyses. The globe was vertically bisected and processed for light and transmission electron microscopy and immunohistochemistry. Results: Comparative analysis of the superior and inferior limbal zones showed a gradual degradation of palisade structures associated with the transition from a hyperplastic to an attenuated corneal epithelium, inflammatory cell infiltrations and basement membrane irregularities. The clinically unaffected inferior part revealed no distinct stem cell clusters in the preserved palisade region, but a uniform population of hyperproliferative, undifferentiated progenitor cells in the basal/suprabasal layers of limbal and corneal epithelia, which gave rise to maldifferentiated epithelial cells exhibiting a conjunctival/epidermal phenotype and nuclear-to-cytoplasmic translocation of Pax6. The structure of the limbal niche was fundamentally perturbed, showing marked alterations in extracellular matrix composition, dislocation of atypical melanocytes lacking melanosomes and melanin, aberrant Wnt/β-catenin and retinoic acid signaling, and massive immune cell infiltration. Conclusions: Considering the limitations of a single Case study, the findings suggest that ocular surface alterations in AAK are caused by a primary dysfunction and gradual breakdown of the limbal stem cell niche through Pax6-related effects on both melanogenesis and epithelial differentiation.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Aniridia-associated keratopathy; Extracellular matrix; Immunohistochemistry; Limbal stem cell niche; Melanocytes; Pax6